Etiological aspects of chronic heart failure on the background of overweight and obesity - Р. P. Bidzilya (Zaporozhye State Medical University, 2016)
In Ukraine, the number of patients with clinically manifested chronic heart failure (CHF) could reach 2 million, which corresponds to the prevalence of the disease in the Russian federation (5% of the adult population). The most important etiologic factors of CHF are coronary artery disease and arterial hypertension (AH) (especially in combination with diabetes mellitus and obesity). Recently, the role of AH in the development of CHF is progressively growing, the risk increases proportionately to degree of AH. Aim. To study the etiological aspects of the CHF on the background of overweight and abdominal obesity depending on gender and age factors, body mass index (BMI), functional class (FC) of the disease and the left ventricle ejection fraction (LVEF), Materials and methods. 250 patients were examined and the medical case reports of 111 patients with CHF of FC I-III of the disease on the background of normal, overweight and abdominal obesity I-III degree were retrospectively analyzed. The patients underwent complex clinical, laboratory and instrumental investigations according to the Recommendations for the diagnosis and treatment of CHF Association of cardiologists of Ukraine and the Ukrainian Association of specialists on heart failure (2012). Results. It is established that ischemic CHF was observed more frequently in men, in elderly and senile age, in normal and overweight, with the higher FC of the disease and a low LVEF. CHF of non-ischemic (hypertensive) etiology was predominant in women, in young, middle and elderly age, accompanied with obesity, lower FC of the disease and preserved LVEF. The combined genesis CHF often occurred in elderly and senile age, in high FC of the disease with low LVEF. Conclusion. The peculiarities of prevalence of ischemic, non-ischemic and combined etiology of CHF in patients with overweight and obesity, and its dependence on gender and age factors, BMI, FC of disease and LVEF are established.